The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/cdn/nzz044.p08-007-19
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of the Effect of Portion Size and Ingestive Frequency on Energy Intake and Body Weight Among Adults in Randomized Controlled Trials (P08-007-19)

Abstract: Objectives Total energy intake is the product of portion size (PS), the energy content of an ingestive event, and ingestive frequency (IF), the number of ingestive events per unit time. An alteration in either portion size or ingestive frequency, that is not compensated by the other, must result in a change in energy intake and, if maintained over time, body weight. The primary objective of this meta-analysis was to assess the independent effects of PS and IF on dietary energy intake and body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Our findings are consistent with the findings of epidemiological studies, which concluded that the consumption of large FPS at one sitting was positively associated with overweight and obesity in adults [77,78].…”
Section: The Consumption Of Large Food Portion Sizessupporting
confidence: 93%
“…Our findings are consistent with the findings of epidemiological studies, which concluded that the consumption of large FPS at one sitting was positively associated with overweight and obesity in adults [77,78].…”
Section: The Consumption Of Large Food Portion Sizessupporting
confidence: 93%
“…Our findings of equal calorie consumption between groups is in line with a meta‐analysis which found no relation between BMI and food intake in the BTT (Robinson et al., 2017). Despite these results, there is an ongoing discussion if ingestion frequency is associated with a higher BMI (Higgins et al., 2019, 2022; Mattes, 2014).…”
Section: Discussionmentioning
confidence: 99%